Answer:
a = - 1.1
Step-by-step explanation:
Condition for a single variable function f(x) to be decreasing is f'(x) < 0.
So, in our case,
.
Then, differentiating with respect to x on both sides we get,
![f'(x) = 4(- 2)\frac{1}{x^{3}} - 6 < 0](https://tex.z-dn.net/?f=f%27%28x%29%20%3D%204%28-%202%29%5Cfrac%7B1%7D%7Bx%5E%7B3%7D%7D%20-%206%20%3C%200)
⇒ ![- \frac{8}{x^{3}} - 6 < 0](https://tex.z-dn.net/?f=-%20%5Cfrac%7B8%7D%7Bx%5E%7B3%7D%7D%20-%206%20%3C%200)
⇒
{Dividing both sides with - 1 and hence the inequality sign changes}
⇒ ![\frac{8}{x^{3}} > - 6](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7Bx%5E%7B3%7D%7D%20%3E%20-%206)
⇒ 8 > - 6x³ {Multiplying both sides with x³}
⇒ 6x³ > - 8 {Interchanging the sides}
⇒ ![x^{3} > - \frac{8}{6}](https://tex.z-dn.net/?f=x%5E%7B3%7D%20%3E%20-%20%5Cfrac%7B8%7D%7B6%7D)
⇒ x > - 1.1
Therefore, a = - 1.1. (Answer)